Development of E-Module for Construction Management Application Course Based on Building Information Modeling (Universitas Negeri Semarang, 2021)
The rapid demands of technological development in the construction world require competent and skilled human resources to operate BIM-based software. One of the university's efforts to address this is by adopting Building Information Modeling in one of the lecture teaching materials, one of which is the Construction Management Application Course. The research and development aim to produce e-modules Building Information Modeling-Based Construction Management Application Course at the Building Engineering Education Study Program, Universitas Negeri Jakarta. The method used in this study is the Research and Development by using a 4D model. The 4D model consists of 4 systematic stages: define, design, development and Dissemination. Based on the validation results, the developed e-modules fall into the very feasible category with 82% of material experts and 93% of media experts. Limited trial results and Dissemination of N-gain values of 0.65 (moderate) and 0.75 (high) show learners' cognitive improvement. Along with the respondents' questionnaire results, the percentage of practicality was 90.2%, which falls into the Very Practical category. Based on the advantages processed, the Construction Management Application e-module regarding the procedures of making 4D and 5D simulations in 2-story house buildings using Autodesk Navisworks software is suitable as advanced teaching materials in the Construction Management Application course.